Deskripsi Kemandirian Anak Ditinjau dari Pola Asuh Orang Tua di TK Dewi Sartika Kecamatan Sipatana Kota Gorontalo - Winrista Minahali; Icam Sutisna; Sri Rawanti (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
Abstract. Winrista Minahali, 2024. Description of Children's Independence Reviewed from Parenting Patterns at Dewi Sartika Kindergarten, Sipatana District, Gorontalo City, Faculty of Education, Gorontalo State University. Supervisor 1: Icam Sutisna, S.Pd., M.Pd and Supervisor II: Sri Rawanti, S.Pd., M.Pd. The formulation of the problem in this study is